THE OVERVIEW OF INDONESIAN MINISTRY OF TRANSPORTATION’S MOBILE GEOGRAPHIC INFORMATION SYSTEM APLICATION - Istiyanto, Bambang; Rizal, Yan El; Rizka, Mouli De; Brilianti, Dani F. (FSTPT Indonesia, 2015)
Traffic information is an important necessity for humans. Advances in technology make various facilities. The use of smart phone is already very common thing. The use of smart phones, especially development based on open source license is very favorable. Any individual or organization can create applications that can be accessed by many people. There are various applications on smart phone device that is associated with the map -based transportation. Staring from the application issued by government agencies to the application made by the individual. One of the legal application based map application issued by the agency is MoT GIS or known as